Web-based Decision Support System for Characters Selection in Game Genshin Impact with SAW Method - Patricia Altanny; Monika Evelin Johan (Ultima InfoSys : Jurnal Ilmu Sistem Informasi, 2023)
Genshin Impact is a game that has lots of amazing playable and time-limited characters. Many F2P players are in a dilemma most of the time, and can’t choose the characters they should draw. This research’s aim is to design and develop a web-based decision support system capable of ranking the best characters based on five combat roles to help F2P fans or player to select the best character, using the SAW (Simple Additive Weighting) method. SAW is capable of choosing the desired criteria (DPS, Heal, Shield, Buff, and Elemental) and each of their weight. The result of the recommendation is for Genshin Impact fans to be able to make a decision on whom they should pull-based. The implementation of this method is in the form of a prototype of a website making it easier for users to use the system anywhere and anytime.